ReaxFF simulations on molecular entrapment capability and gas sensor performance of some volatile organic compounds by a novel functional tubular-helix nanostructure doped sulfur - Celik, Fatih Ahmet; Yilmaz, Mucahit; Karabulut, Ezman (Springer Heidelberg, 2026)
In this study, we employed the advanced reactive force field (ReaxFF) molecular dynamics (MD) simulations to investigate the adsorption mechanisms of acetone, ethanol, methanol and propanol molecules on newly-designed tubular helix nanostructure doped by sulfur substituting carbon atoms. The adsorption processes of four different volatile organic compounds (VOCs) on tubular helix nanostructure are simulated at temperature of 300 K, containing fixed 100 adsorbate molecules. The adsorption energy of acetone is calculated as -4.4 eV which is higher than that of other molecules and it exhibits very strong adsorption of acetone on active sites of tubular helix nanostructure attracting this molecule. Moreover, some MD structural analysis methods, such as partial correlation function (PCF) and diffusion coefficients from mean square displacement (MSD) reveal that O atom in acetone molecule strongly interactions with C and S atoms on tubular helix nanostructure in short distance of 1.17 & Aring;. Addition, the diffusion coefficient of acetone molecule into tubular helix nanostructure is more than that of other molecules indicating faster and easier movement in helical environment. Finally, molecular entrapment capability of tubular helix nanostructure and the surrounding level of acetone molecules the tubular helix nanostructure were revealed by computational method. The computational results help understand the great potential of gas sensor device of newly-designed tubular helix nanostructure in the context of pioneer experimental studies.
Keywords: ReaxFF-MD simulations; Tubular helix nanostructure; Gas adsorption; Volatile organic compounds